EFFICIENCY ANALYSIS OF RAW MATERIAL INVENTORY AT SEMPULUR PRATAMA KLATEN - Insiyah, Yumawati (Management, 2010)
This study aims to determine the efficiency of raw material inventory at PT. Primary Sempulur Klaten during 2003. The study was a descriptive study that describes the state of the company relating to raw materials, and then described in written form. This study used data collection method with observation and interviews. Methods of data analysis used is the method most economical purchase amount (EOQ), rescue supplies and Reorder Point. From the results of this study concluded that the raw material inventory at PT. Sempulur Pratt has not shown the existence of inventory cost efficiency. This happens because the company has not used the EOQ method in the purchase of raw materials. Inventory cost efficiencies can be achieved if companies use EOQ method is Rp.36.376.913, while the most economical purchase quantity is 9 times, waiting time the most efficient way to purchase raw materials was 5 days in which the 5-day waiting period, the company may issue The most economical cost that is equal Rp.1.886.013. Key words: efficiency, raw materials, EOQ, inventory savior, reorder point